Dermatology Treatments and their Effects on Patch Testing (Canadian Dermatology Today, 2024)
Patients are often sent for patch testing to rule out allergic contact dermatitis, but it is a clinical conundrum of what to do when they are on systemic agents. The clinical question is, should the systemic agents be held for 4-5 half-lives and then patch tested to ensure there is no blunting of the immune system? The reality is that in this population without systemic treatments, patients are seldom clear enough to patch test. Their backs are covered in dermatitis and testing runs the risk of eliciting an uninterpretable “angry back”. The other consideration is patients’ strong preference to remain on systemic medications that control their significant itch, rash and associated sequelae. In an ideal world, it would best to patch test patients prior to the initiation of a systemic agent but clinically this is not always feasible. We will explore various clinical scenarios involving patch testing and discuss the advice the dermatologist should provide patients regarding holding their medications.